Corporate Governance Moderates the Relationship of Information Asymmetry and Dividend Policy Towards Earnings Management - Eka Berlianti, Novita; Nur Laela Ermaya, Husnah; Guritno, Yoyoh (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2022)
In determining accounting profit, managers need to use certain assumptions and estimates in accordance with applicable accounting standards. This can lead to different treatment between transactions with one another and increase the potential of the management to implement earnings management in order to fulfill their personal interests. The difference in information related to the condition of the company and the interests between managers and shareholders is allegedly a factor that determines the occurrence of earnings management. Thus, this study was conducted to examine the effect of information asymmetry and dividend policy on earnings management, and how the role of corporate governance in moderating the relationship between information asymmetry and dividend policy on earnings management. The sample in this study were 46 banking companies listed on the Indonesia Stock Exchange for the 2015-2019 period and were selected using the purposive sampling method. The final sample used in this study were 9 banking companies. The test results using Fixed Effect Generalized Least Square (FEGLS) regression showed that: (1) Information asymmetry had no significant effect on earnings management; (2) Dividend policy has a significant negative effect on earnings management; (3) Corporate governance cannot moderate the relationship between information asymmetry and earnings management; (4) Corporate governance cannot moderate the relationship between dividend policy and earnings management.